Quality Management Strategy in Improving Educational Institution Accreditation Results - Muhammad Alfi Alfaridli; Dian Zulfatul Iman; Ummi Hani’ (PENG: Jurnal Ekonomi dan Manajemen, 2025)
\ This study focuses on quality management strategies in improving the accreditation results of educational institutions, by examining in depth how managerial practices are implemented systematically and sustainably. The approach used is qualitative with a case study type, which allows for in-depth exploration of the process, dynamics, and context of implementing quality strategies at Madrasah Aliyah Nurul Jadid which has obtained "Very Good" accreditation. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation studies, which were analyzed using the Miles and Huberman interactive analysis model. The results of the study indicate that self-evaluation-based planning, strengthening the role of the Internal Quality Assurance Team (TPMI), data-based monitoring and evaluation, and training to improve teacher and education personnel competencies are key strategies that directly contribute to achieving better accreditation. These findings provide important implications for the development of an educational quality management system that does not only focus on administrative fulfillment, but also on the internalization of a sustainable quality culture. This study also recommends the importance of integration between reflective and data-based practices in the quality assurance system in educational units..